2004
DOI: 10.1016/j.pain.2004.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Neck pain in adolescence. A 4-year follow-up of pain-free preadolescents

Abstract: The main aim of this study was to explore the occurrence and changes of neck pain in pain-free preadolescents. The evaluation was performed at 1- and 4-year follow-ups. Of the pain-free preadolescents, 366 (71.9%) completed structured pain questionnaires at 1 and 4 years. The occurrence of neck pain at least once a month was 21.3 and 43.4% and at least once a week was 6.3 and 19.4%. Sex difference was found only at the 4-year follow-up, when subjects were 13-16-year-old. Neck pain was then more common among gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 21 publications
3
38
0
Order By: Relevance
“…Absence of such associations might be due to the possibility for gender-and/or age-dependent differences in the presence and dominance of posture as a contributing factor within the widely accepted multifactorial nature of spinal pain. Factors that come into play might include biological, mechanical, psychological, cognitive and social factors [11][12][13][14][15][16][17][18][19][20][21]. Alternatively, the association between postural types and spinal pain in pre-PHV boys yet not in girls might suggest that habitual stance in these populations involves different biomechanical loading patterns (see below).…”
Section: Discussionmentioning
confidence: 99%
“…Absence of such associations might be due to the possibility for gender-and/or age-dependent differences in the presence and dominance of posture as a contributing factor within the widely accepted multifactorial nature of spinal pain. Factors that come into play might include biological, mechanical, psychological, cognitive and social factors [11][12][13][14][15][16][17][18][19][20][21]. Alternatively, the association between postural types and spinal pain in pre-PHV boys yet not in girls might suggest that habitual stance in these populations involves different biomechanical loading patterns (see below).…”
Section: Discussionmentioning
confidence: 99%
“…The similarity of risk factors causing the onset of symptoms and their persistence has been reported in other studies 17,18) . Ståhl et al 45) found that frequent musculoskeletal pain or physical and psychological symptoms, such as headache, depressive mood and sleep difficulties, were risk factors of the occurrence and persistence of weekly neck pain during a 4 year follow up. Our results suggest that female gender plays a dominant role in relation to thoracic spine pain in undergraduate students.…”
Section: Discussionmentioning
confidence: 99%
“…Nine of these were rated as scientifi cally admissible for inclusion in a best evidence synthesis, regarding incidence rates for neck pain in the general population [40,[49][50][51][52][53][54][55][56]. According to these, the one year incidence for activity-limiting neck pain ranged from 1.7 % to 11,5 %.…”
Section: Men (N=271)mentioning
confidence: 99%